2007
DOI: 10.1002/pen.20748
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and tribological behaviors of polyamide 66/ultra high molecular weight polyethylene blends

Abstract: The blends of polyamide (PA) and ultra high molecular weight polyethylene (UHMWPE) were prepared by a Brabender DSE25 co-twin screw extruder, and maleic anhydride (MAH) grafted high-density polyethylene (HDPE) was used as a compatibilizer. A chemical reaction between MAH group of MAH-g-HDPE and terminal amino group of PA was testified by FT-IR analysis. Mechanical and tribological tests showed that the tensile and bending strength of PA decrease with the increase of UHMWPE. Besides, the mechanical strengths of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…) has some dispersion capability during processing though it is still poor. Practically, two different routes could be adopted to obtain more uniformly dispersed blends, first by using different screw designs with more shear and elongation effects though it may cause some thermal degradation of the TPU matrix at the same time, second by the incorporation of the compatibilizer to reduce the interfacial adhesion of the two components . Also, select UHMWPE with lower molecular weight is an alternative choice though at the expense of decreasing the mechanical and tribological properties.…”
Section: Resultsmentioning
confidence: 99%
“…) has some dispersion capability during processing though it is still poor. Practically, two different routes could be adopted to obtain more uniformly dispersed blends, first by using different screw designs with more shear and elongation effects though it may cause some thermal degradation of the TPU matrix at the same time, second by the incorporation of the compatibilizer to reduce the interfacial adhesion of the two components . Also, select UHMWPE with lower molecular weight is an alternative choice though at the expense of decreasing the mechanical and tribological properties.…”
Section: Resultsmentioning
confidence: 99%
“…7,6,[31][32][33][34][35] The improvements of the wear resistance were due to either mechanical or chemical reasons. Wang et al 36 studied the mechanical and tribological behavior of the blend of PA66/UHMWPE with MAH-g-HDPE as compatibilizer. The results showed that the addition of UHMWPE reduced the wear rate.…”
Section: Introductionmentioning
confidence: 99%
“…Although they introduce a restoring force into the sliding system, the design of the frictional coefficients and stiffness of the restoring device both have an essential impact on the isolation performance. In this case, a number of self‐lubricant materials such as polytetrafluoroethylene (PTFE), ultrahigh molecular weight polyethylene, polyformaldehyde (POM), and other thermoplastics have been proposed for facilitating the workability of sliding surface . However, the choice of materials is significant because the tribological behavior varies from material to material.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, a number of selflubricant materials such as polytetrafluoroethylene (PTFE), ultrahigh molecular weight polyethylene, polyformaldehyde (POM), and other thermoplastics have been proposed for facilitating the workability of sliding surface. [17][18][19] However, the choice of materials is significant because the tribological behavior varies from material to material. Moreover, the sliding condition of the bearing matters as well, for example, the coefficient of friction reduces after three cycles of loading at high velocities 20,21 ; abnormal sliding behavior like stick-slip influences the characterization of friction behavior.…”
mentioning
confidence: 99%